Children's services in Philippine public libraries status and prospects - Cruz, Prudenciana C. (1995)
This is a descriptive study of children's service in Philippine public libraries. The 1993 Directory of Public Libraries put out by the Public Libraries Division of the National Library has a total of 523 public libraries broken down as follows: 1 regional, 41 provincial, 32 city, 389 municipal libraries, and 60 barangay, district, or deposit station libraries. Of this number, 34 provincial, 29 city and 91 municipal libraries or a total of 154 public libraries were surveyed. One hundred one questionnaires were returned.